Sentidos e significados do cuidado de si realizado por psicoterapeutas: reflexão sobre individuação, cuidado de si, qualidade de vida e fazer psicoterápico - Souza, Diego Gessualdo Sabádo de (2018)
The process of becoming oneself, which we have named becoming an individual, carries out the process of individuation, of assumption of its singular and subjective essence, of becoming the self that is, presents itself as the fundamental objective of the psychological clinic. Even if it is not designated as a primary objective, the encounter, discovery, understanding and self-assumption (individuation process) permeates the actions and practices of the psychologist, sustains and grounds encounters in psychotherapy, always and in a " one, "singular. Our research is concerned with the psychotherapist and how he performs his process of individuation. Linked to the process of individuation, we have, as the "continuum" of the self in existence, as the maintenance of that individuation, the care of self. The person as existing realizes in his projects of being, these projects are possible from the "I" of each person singularized, this human being in his relationship with the world deals with this world, but in his relation to himself worry. This pre-occupation is performed in self care. To investigate and reflect on how psychotherapists understand and take care of themselves and how they perceive the repercussion of this care in their performance in psychotherapy is the goal of our thesis. The research, with a qualitative character and phenomenological methodology, follows the indications of Amatuzzi (2009) for the performance of phenomenological research in psychology. We divide the research into two moments, in the first part we intend to carry out philosophical reflection, as a fundamental ontology, of these two phenomena: individuation and self-care, as well as the quality of life and the psychotherapeutic doing itself. In the second part we intend to go to the psychotherapists and, in three meetings with each one, where we will perform 1. the application of the Langoni and Bassani Quality of Life Instrument of Evaluation (2016), 2. an interview and 3. a reflexive dialogue, to produce, together with these psychotherapists and from their own understandings, new ways of placing the problem and the phenomena of individuation and self-care, in harmony with the basic notion that both are by nature subjective phenomena. The research has CNPQ support